Cost-effectiveness analysis of routine 13-valent pneumococcal conjugate vaccinations in Chinese infants. Issue 6 (3rd June 2018) - Zhou, Hua; He, Jinchun; Wu, Bin; Che, Datian
ABSTRACT: Background: This study aimed to evaluate the cost-effectiveness of the 13-valent pneumococcal conjugate vaccine (PCV-13) compared to a no vaccination strategy in Chinese infants. Methods: A Markov process model was developed to examine the outcomes of PCV-13 against a no vaccination strategy using data and assumptions adapted for relevance to China. Outcomes over a lifetime horizon are presented. One-way and probabilistic sensitivity analyses were performed to determine the uncertainty. Results: Compared to no vaccination, a PCV-13 vaccination program would provide a gain of 0.009 additional quality-adjusted life years (QALYs) per subject. From the health care and societal perspectives, the incremental costs per QALY were $20, 709 and 18, 483, respectively. When herd effect was included, the cost effectiveness of the PCV-13 vaccination strategy was notably improved. The lower price of PCV-13 will improve the cost-effectiveness. Conclusions: The PCV-13 vaccination is likely to be cost-effective at the current Chinese prices and ceiling threshold ($8, 382).